Estado, elite e sociedade na política da Rússia para a Ucrânia - Menezes, Gustavo Oliveira Teles de (2024)
This thesis analyzes the role of the configuration of the Ukrainian state, state-society relations in Ukraine and relations with members of Ukraine’s political elite and society in Russia's Ukraine policy in the post-Soviet era (1991-2024). The research sought to answer the following questions: how the issues of the configuration of the Ukrainian state, state-society relations in Ukraine and relations with members of Ukraine’s political elite and society were present in Russia's Ukraine policy throughout the analyzed period? How did Russia interact with members of Ukraine’s political elite in order to achieve its goals in that country? How did processes and events related to the configuration of the Ukrainian state, state-society relations in Ukraine and Ukraine's political elite affect Russia's perspectives and actions regarding the 2013-2014 crisis and Russia’s large-scale invasion of Ukraine launched in 2022? The research argues that the configuration of the Ukrainian state, state-society relations in Ukraine and relations with members of Ukraine’s political elite and society were seen by Russia as important factors in the conceptualization of Moscow's influence and interests in Ukraine. Furthermore, the work points out that Russia involved itself in the power dynamics within Ukraine’s political elite in order to achieve its goals in Ukraine, in a process conditioned by Russia’s perceptions of its own interests and capabilities. Finally, the thesis argues that actual or potential transformations in the configuration of the Ukrainian state, in state-society relations in Ukraine and in the composition of Ukraine's political elite influenced Russia’s perspectives and actions in 2013-2014 and 2022. The research employs Transnationalist and Elite Theory approaches, drawing attention to the role of political actors and organizations beyond central governments at the national level. With its thematic framework and theoretical-methodological approach, the research aims to contribute to filling gaps in the literature on Russia-Ukraine relations and provide elements for the understanding of the power dynamics related to this theme, which has attracted significant attention from society and generated a major impact on international security dynamics